Gut–Brain Axis in Depression: A Narrative Review of Microbiome Signatures, Mechanisms, Biomarkers, and Microbiota-Targeted Interventions - Ślinko, Izabela; Panas, Zuzanna; Dryl-Jarmoc, Ewa; Kuliś, Gabriela; Zimowski, Mateusz; Dziemiańczuk, Jakub; Czajkowski, Mateusz; Krawczuk, Kacper; Kadysz, Piotr; Kolanek, Agata (Quality in Sport, 2026)
Background. The microbiota–gut–brain axis (MGBA) is a key pathway in the pathophysiology of depression, integrating neural, immune, and metabolic mechanisms and influencing processes relevant to mood regulation. Aim. This narrative review summarizes current evidence on the role of the MGBA in depression, including microbial composition, functional pathways, biomarkers, and therapeutic interventions. Material and methods. A literature search was conducted in PubMed and PMC (2018–March 2026, including key earlier studies). The review focused on microbial alterations, metagenomic functions, intestinal barrier and immune biomarkers, microbial metabolites, and clinical trials. Results. Cohort studies show associations between depressive symptoms and gut microbial taxa involved in neuroactive pathways; however, findings are heterogeneous and of limited diagnostic value. Experimental studies support causality, as microbiota from patients with major depressive disorder induce depression-like behaviors in rodents. Vagal nerve integrity appears necessary for some microbiota-mediated effects, and stress-related dysbiosis may contribute to microglial activation and impaired neurogenesis. Biomarker studies indicate increased intestinal permeability and elevated markers of microbial translocation (e.g., zonulin, LPS-binding protein, sCD14), though their clinical utility remains unclear. Clinical trials suggest probiotics may reduce depressive symptoms as adjunctive therapy, while evidence for prebiotics is inconsistent and fecal microbiota transplantation remains experimental. Conclusions. The MGBA plays an important role in depression, but further standardized and longitudinal studies are needed to clarify mechanisms and support clinical applications, particularly for personalized therapies.